Revolution in the perspective of khilafah - Zainuddin Losi; Asriani Asriani; Andi Nur Fiqhi Utami; Nizar Nizar (Indonesia Prime, 2021)
The collapse of the Khilafah in 1924 caused Hizb ut-Tahrir (HT) to fight for the re-establishment of the Khilafah. The expected change in the struggle is a fundamental change to people's thinking, outlook on life and system of government so that the change is more appropriately referred to as revolution. This paper examines HT's perspective on the method of revolution based onthe stages of the Prophet's da'wah. Thisresearch reveals that the revolution in ht perspective is applied through 3 (three) stages of da'wah, namely (1) wiring; (2) Interaction with Society, which includes "Battle of Thought" and "Political Struggle"; and (3) Acceptance of Power which includes Thalabun Nushrah for the Purpose of Support against Da'wah and Thalabun Nushrah for the Purpose of Handover of Power. Numbers (1) and (2) are categorized as "Methods of Thought Revolution". Number (3) is categorized as the "Method of System Revolution". Stages of da'wah above are carried out through da'wah fikriyah (da'wah ikiran)which has implications for changes in the thinking of thecommunity and public awareness, and is done Peacefully and without violence. The three stages of da'wah were adopted by HT from the prophet's da'wah stage